PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN DANA BAGI HASIL TERHADAP PENGALOKASIANBELANJA MODAL - Gagas Tyas Rudatin, 09.05.52.0042; Kartika, Andi (Students Journal of Accounting and Banking, 2014)
This study aims to test the influence of local revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK) and DBH (DBH) of the Allocation of Capital Expenditure. The population in this study is the government district / town in Central Java consists of 35 regencies / cities 2009-2011. This study uses secondary data secondary taken from the Central Bureau of Statistics (BPS) of Central Java 2009-2011. Testing this hypothesis using multiple linear regression with t test, F test, and the coefficient of determination. Research results show that the PAD and DAU significant positive effect on capital expenditures. DAK is no significant positive effect on capital expenditures, and while DBH negatife insignificant effect on capital expenditures. For local government is expected to further improve and attention DAK components and DBH in order to increase the allocation for capital expenditure that can be added. Keywords: capital expenditures, the General Allocation Fund, Special Allocation Fund, revenue, revenue sharing